Current Perspective on the Therapeutic Preset for Substance-Assisted Psychotherapy - Thal, Sascha B.; Bright, Stephen J.; Sharbanee, Jason M.; Wenge, Tobias; Skeffington, Petra M. (Frontiers in Psychology, 2021)
The present narrative review is the first in a series of reviews about the appropriate conduct in substance-assisted psychotherapy. It outlines a current perspective onpreconditions and theoretical knowledge that have been identified as valuable in the literaturefor appropriate therapeutic conduct in substance-assisted psychotherapy. In this context, considerations regarding ethics and the spiritual emphasis of the therapeutic approaches are discussed. Further, current methods, models, and concepts of psychological mechanism of action and therapeutic effects of substance-assisted psychotherapy are summarized, and similarities between models, approaches, and potential mediators for therapeutic effects are outlined. It is argued that a critical assessment of the literature might indicate that the therapeutic effect of substance-assisted psychotherapy may be mediated by intra- and interpersonal variables within the therapeutic context rather than specific therapeutic models per se. The review provides a basis for the development and adaptation of future investigations, therapeutic models, training programs for therapists, and those interested in the therapeutic potential of substance-assisted psychotherapy. Limitations and future directions for research are discussed.